Marital interactions in partners of ostomized patients - Silva,Ana Lúcia da (2014)
Objectives:The present study aimed to investigate the sociodemographic profile of ostomized patients, describe their daily marital interactions, and identify these individuals' health demands.Method:The present investigation consisted of a descriptive and quantitative study of partners of ostomized patients.Results:A total of 36 individuals were interviewed, of whom 24 (66.7%) were female. Participants were aged between 31 and 70 years, and reported an annual family income of $20,000. The present study found that the stoma surgery did not lead to significant changes in marital relationships. The study participants appeared to be significantly invested in overcoming the barriers imposed by their partner's condition. Respondents also demonstrated dedication, sensitivity and a willingness to help their partner adapt to physiological and gastrointestinal changes.Conclusion:The changes following stoma surgery also have an impact on patients' partners, and both individuals must work together to keep it a secret if necessary. The present results made it clear that respondents empathized with their partners, and agreed that undergoing stoma surgery is a difficult ordeal.